Liver Transplantation for Acute Liver Failure at 11-Week Gestation with Successful Maternal and Fetal Outcome - Vinaya C. Maddukuri; Courtney D. Stephenson; Lon Eskind; William A. Ahrens; Preston Purdum; Mark W. Russo (Case Reports in Transplantation)
Acute liver failure (ALF) during pregnancy is very uncommon. Pregnancy-specific liver conditions like hemolysis, elevated liver enzymes, and low platelets (HELLP) syndrome and acute fatty liver of pregnancy can cause ALF at term or postpartum, but, typically occur during the third trimester. Most of these patients recover spontaneously after delivery, but, on occasion, they require liver transplantation in the postpartum period. However, ALF during the first and second trimester of pregnancy requiring antepartum liver transplantation is rare. Only fifteen cases of liver transplantation during pregnancy have been reported, and very few occurred during the first trimester. We report a Woman who developed acute liver failure during the first trimester of pregnancy and underwent successful liver transplantation at 11-week gestation, followed by successful delivery of the fetus at 30 weeks. To our knowledge, this is the earliest case of successful liver transplantation during pregnancy followed by successful fetal outcome. We discuss management of the patient and fetus before, during, and after liver transplantation and review the literature on antepartum liver transplant in pregnancy.